2007
DOI: 10.4018/jkm.2007040104
|View full text |Cite
|
Sign up to set email alerts
|

Improving KMS Acceptance

Abstract: The purpose of this article is to contribute to the improvement of the acceptance of information systems (IS) devoted to the codification and sharing of knowledge (a type of knowledge management systems [KMS]). A research model was developed through a multi-staged, multi-method research process and its test supports the hypotheses that the acceptance of KMS is determined, in addition to the classical constructs of the technology acceptance model (TAM), by a few organizational factors, and by the influence exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 55 publications
4
16
2
Order By: Relevance
“…The finding is in line with previous research (Bock et al, 2005;S. Liao & Chou, 2012;Vitari, Moro, Ravarini, & Bourdon, 2007).…”
Section: Structural Modelsupporting
confidence: 83%
“…The finding is in line with previous research (Bock et al, 2005;S. Liao & Chou, 2012;Vitari, Moro, Ravarini, & Bourdon, 2007).…”
Section: Structural Modelsupporting
confidence: 83%
“…These results also noted that promoting knowledge sharing concentrated intrinsic reasons rather than extrinsic motivations or financial rewards. The study revealed a low incidence in knowledge sharing practices compared to the NPOs and for-profit organization, which contradicted previous research that reward and recognition systems enhance knowledge sharing (Vitari et al, 2007;Vuori and Okkonen, 2012).…”
Section: Extrinsic Motivational Factorscontrasting
confidence: 99%
“…In addition, studies have also described the positive association between the level of employees' perception on the degree of management commitment in supporting KM initiatives with the extent to which a knowledge sharing culture exists in an organization (Benbya and Belbaly, 2005). Similarly, management's commitment to communicating the organizational benefits achieved by sharing knowledge has been found to possess a positive impact on the use of KMS in an organization (Vitari et al, 2007). As concerns to this discussion, the hypotheses given below are suggested: H5.…”
Section: Management Commitmentmentioning
confidence: 99%
“…Particularly, some of the studies have acquired their set of determinants from both quantitative and qualitative techniques (Aurum et al, 2007;Kulkarni et al, 2007;Vitari et al, 2007), others have advanced their determinants set from quantitative surveys only (Alavi and Leidner, 1999;Butler et al, 2007), while the rest of the studies have identified their set of determinants based on qualitative analysis (Benbya and Belbaly, 2005;Davenport et al, 1998;Moffett et al, 2004;Mohamed et al, 2006). All the determinants from these studies were compiled, analyzed, and listed in Table 1.…”
Section: Determinants For Kms Adoptionmentioning
confidence: 99%
See 1 more Smart Citation